2007
DOI: 10.1063/1.2713085
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between detailed and configuration-averaged collisional-radiative codes applied to nonlocal thermal equilibrium plasmas

Abstract: A collisional-radiative model describing non-local-thermodynamic-equilibrium plasmas is developed. It is based on the HULLAC suite of codes for the transitions rates, in the zero-temperature radiation field hypothesis. Two variants of the model are presented, the first one is configurationaveraged, while the second one is a detailed level version. Comparisons are made between them in the case of a carbon plasma; they show that the configuration-averaged code gives correct results for an electronic temperature … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…However, the CG algorithm may lack of robustness. For instance, we considered the case where radiative and autoionization rates are canceled: including only the collisional excitation and ionization and the reverse processes, and comparing the solution with Saha-Boltzmann is a way to check the algorithm accuracy [17]. In a krypton plasma at a 500 eV temperature and 10 14 cm −3 electronic density, with 5 662 levels and 14 charge states accounted for, we did obtain 3 populations different from Saha-Boltzmann by 2 × 10 −13 in average (6 × 10 −10 at maximum), but this was obtained after a rather large number of iterations: 1966 with ε = 10 −13 in Eq.…”
Section: Conjugate Gradients Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the CG algorithm may lack of robustness. For instance, we considered the case where radiative and autoionization rates are canceled: including only the collisional excitation and ionization and the reverse processes, and comparing the solution with Saha-Boltzmann is a way to check the algorithm accuracy [17]. In a krypton plasma at a 500 eV temperature and 10 14 cm −3 electronic density, with 5 662 levels and 14 charge states accounted for, we did obtain 3 populations different from Saha-Boltzmann by 2 × 10 −13 in average (6 × 10 −10 at maximum), but this was obtained after a rather large number of iterations: 1966 with ε = 10 −13 in Eq.…”
Section: Conjugate Gradients Methodsmentioning
confidence: 99%
“…The matrix condition 4 is checked inside the code and it was found satisfactory in every considered cases. As an accuracy test proposed before [17], we solved with the LU algorithm a kinetic system of 4481 equations including only collisional excitation, collisional ionization plus the reverse processes. One gets then the Saha-Boltzmann solution with a maximum population difference of 1.2 × 10 −12 , and an average difference of 5.4 × 10 −16 , the Gauss algorithm providing the same excellent accuracy.…”
Section: Lu Decompositionmentioning
confidence: 99%
“…This is what is implicitly hidden in the expression (23). This is not a straightforward task for complex codes such as those based on the superconfiguration approach [7,8] or for approach intending to explicitly check the validity of the configuration average procedure [9,10]. As for the total ion energy, we have other trends for the relaxation towards the steady-state.…”
Section: Numerical Applicationsmentioning
confidence: 97%
“…As reported in Lucy (2001), the super level method applying to a system with ∼ 1000 levels can reach an accuracy of 0.1 with 6 iterations, and 0.01 with 20 iterations. Meanwhile, Poirier & de Gaufridy de Dortan (2007) showed that the super level method, as adopted in G03, might become less accurate when the rms deviation of transition rates inside one super level increases.…”
Section: Comparing With G03mentioning
confidence: 99%